Optimum flow rate enhances the performance of lettuce (Lactuca sativa L.) in hydroponic culture - Abbas, Sibtain; Younas, Muhammad; Zafar, Nawal; Munir, Muhammad Kashif; Sekar, Ajay Kumar; Asif, Muhammad; Hussain, Sadam; Rabbani, Muhammad Umar; Faheem, Muhammad; Irshad, Muhammad Qavi; et al. (Plant Science Today, 2024)
Poor substate flow rate affects the production of crops under hydroponic systems as contact and collision times of ions (nutrients) with roots is affected deciding nutrients uptake rate and quantity required for crop growth. Keeping in view, a study was conducted under hydroponic culture to obtain optimal flow rate for higher production of lettuce, which is an important leafy vegetable. Two lettuce varieties (Boston and Lollo Bionda) were subjected to 4 different flow rates (0.5, 1.0, 1.5, 2.0 L min-1) under completely randomized design (CRD) with factorial arrangement and replicated four times. The outcomes of the study suggest that performance of Lollo Bionda variety was better than Boston regarding root and shoot fresh and dry biomass, leaf number, area, length and width and head diameter and plant height. The same parameters kept on increasing with increase of flow rate and achieved maximum values at 1.5 L min-1. Beyond that flow rate the values for these parameters declined which indicated that the optimal flow rate for these 2 lettuce verities is 1.5 L min-1. Hence, it was concluded that for higher production of lettuce, the flow rate should be kept at 1.5 L min-1 in Nutrient Film Technique (NFT) using hydroponic system with environmental and substrate conditions mentioned in materials and method portion of this article.